Measuring the Health of Philadelphia’s City Council Districts - Tamara Rushovich; Amber Bolli; Alina Schnake-Mahl; Stephanie M. Hernandez (Journal of Urban Health, 2026)
Abstract Analyzing data by geopolitical districts, like congressional districts, is increasing in popularity in public health monitoring and evaluation but remains relatively rare compared to geographies such as census tracts and counties. In this study, we use city council districts in the City of Philadelphia to illustrate the utility and importance of investigating public health metrics by local political districts. We report on two metrics—tree canopy coverage and health insurance coverage—by city council district and census tract. We discuss the variation within and between districts to show heterogeneity across the city. Lastly, we discuss ways that data can be made accessible to the public through an online dashboard to support advocacy with local politicians.